From clinic to concentration camp reassessing Nazi medical and racial research, 1933-1945 - Weindling, Paul 1953- (The history of medicine in context, 2017)
Inhaltsverzeichnis: Part One: Contexts -- 1. Introduction: A New Historiography of the Nazi Medical Experiments and Coerced Research / Paul Weindling -- 2. The use and abuse of medical research ethics : The German Richtlinien : guidelines for human subject research as an instrument for the protection of research subjects and of medical science, ca. 1931-1961/64 / Volker Roelcke -- 3. The Society of German Neurologists and Psychiatrists and Research in the Context of Eugenics and "Euthanasia" / Hans-Walter Schmuhl -- Part Two: Clinics and the Sciences -- 4. Research on the Boundary between Life and Death : Coercive Experiments on Pregnant Women and their Foetuses during National Socialism / Gabriele Czarnowski and Sabine Hildebrandt -- 5. August Hirt and the supply of corpses at the Anatomical Institute of the Reichsuniversität Strassburg (1941-1944) / Raphael Toledano -- 6. Nazi Anthropology and the Taking of Face Masks : Face and Death Masks in the Anthropological Collection of the Natural History Museum, Vienna / Margit Berner -- 7. Beyond Spiegelgrund and Berkatit : Human Experimentation and Coerced Research at the Vienna School of Medicine, 1939 to 1945 / Herwig Czech -- 8. Murdering the Sick in the Name of Progress?: The Heidelberg Psychiatrist Carl Schneider as a Brain Researcher and "Therapeutic Idealist" / Maike Rotzoll and Gerrit Hohendorf -- 9. Der Kinderfachabteilung vorzuschlagen: The selection and elimination of children at the Youth Psychiatric Clinic Loben (1941-1945) / Kamila Uzarczyk -- Part Three: Concentration Camps -- 10. Children as Victims of Medical Experiments in Concentration Camps / Astrid Ley -- 11. The story of how the Ravensbrück "Rabbits" were captured in photos / Aleksandra Loewenau -- 12. Rascher and the "Russians": Human Experimentation on Soviet Prisoners in Dachau - A New Perspective / Nichola Farron -- 13. Heissmeyer's forgotten victims : Tuberculosis experiments on adults in Neuengamme, 1944-1945 / Anna von Villiez -- Part Four: Legacies -- 14. From Witness to Indictee : Eugen Haagen and his Court Hearings from the Nuremberg Medical Trial (1946-47) to the Stutthof Medical Trials (1952-1954) / Christian Bonah and Florian Schmaltz -- 15. Informed Testimonies: Physicians' Accounts of Nazi Medical Experiments in the Context of Early Czechoslovak War Crimes Investigations, 1945-1948 / Michal V. Simunek -- 16. Post-war Legacies, 1945-2015: Victims, Bodies, and Brain Tissues / Paul Weindling